CONSTITUTIONAL PERSPECTIVE ON THE RIGHT TO PERSONAL HEALTH SOVEREIGNTY AND THE RIGHT TO PERSONAL HEALTH CARE DECISION-MAKING (COMPARATIVE ASPECT OF EUROPEAN PRACTICE) - Reminska, Yuliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose is to provide a comprehensive constitutional analysis of health sovereignty, emphasising the evolution of individual autonomy in healthcare decision-making, while considering state responsibilities in collective health policies. A multidisciplinary methodology combines constitutional law methods, comparative legal studies, and doctrinal analysis, focusing on international frameworks like the ECHR, the Oviedo Convention, and jurisprudence from constitutional review bodies in Germany, Italy, and beyond. The study identifies key constitutional approaches to balancing personal autonomy and public health imperatives. These include the balancing rights approach, which evaluates individual and collective health rights in conflict, such as in mandatory vaccination cases; the proportionality test, ensuring state restrictions on health choices are necessary and minimally intrusive; and substantive due process, safeguarding fundamental rights like bodily integrity and privacy against unjustified state intervention. The findings highlight informed consent as a procedural cornerstone of health sovereignty, ensuring individuals receive sufficient information to make autonomous health decisions. Comparative analysis of European practices offers models for legislative improvements, incorporating proportionality, non-discrimination, and relevant procedural safeguards. Ultimately, this research advances the understanding of health sovereignty as a constitutional principle. It emphasises the dual imperatives of respecting individual autonomy and meeting public health objectives, particularly in the face of global crises and the digitalisation of healthcare systems. The normative framework outlined affirms health sovereignty as a vital aspect of human dignity and democratic governance, requiring harmonised approaches to protect both personal freedoms and societal resilience.